2020
DOI: 10.1111/jfpp.15057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rosemary ( Rosmarinus officinalis L.) supplementation on fresh cheese: Physicochemical properties, antioxidant potential, and sensory attributes

Abstract: Rosmarinus officinalis L. leaves can be valorized by their uses in the production of healthy foods. Rosemary powder and its lyophilized ethanolic extract at different concentrations (g/100 g) were used for the formulation of fresh cheeses: powder cheeses (B: 0.25%, C: 0.5%, D: 0.75%), extract cheeses (E: 0.25%, F: 0.5%) and control cheese (A: 0%). The ethanolic extract was obtained under the optimum conditions of microwave‐assisted extraction (MAE) using response surface methodology (RSM) coupled with a Box–Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…While component 2 (PC2, Figure4), which accounted for 26.61% of the variance, is exclusively represented by electrical specific energy consumption (SECe).The PCA results (Figure4) showed that there was a very significant correlation between the kinetic parameters each other and with energy consumption, namely, between drying rate (DR) and effective diffusivity (D eff ) (r = .99), between drying rate (DR) and energy efficiency (EE) (r = .99), and between effective diffusivity (D eff ) and energy efficiency (EE) (r = .99).It has also been shown that the TPC correlates with antioxidant activity, whether with DPPH (r = .79) or ABTs (r = .90). Similar results have been found by many researchers, namely,Zhao, Yang, Wang, and Lu (2009),Bushra (2012),Lim, Pang, Yusoff, Mudalip, andGimbun (2019), andHimed-Idir et al (2021). Nevertheless,Zheng and Wang (2001) suggested that not only the level of antioxidants but also a synergy between them and other plant constituents could influence the difference in the antioxidant capacity of plant extracts.…”
supporting
confidence: 84%
“…While component 2 (PC2, Figure4), which accounted for 26.61% of the variance, is exclusively represented by electrical specific energy consumption (SECe).The PCA results (Figure4) showed that there was a very significant correlation between the kinetic parameters each other and with energy consumption, namely, between drying rate (DR) and effective diffusivity (D eff ) (r = .99), between drying rate (DR) and energy efficiency (EE) (r = .99), and between effective diffusivity (D eff ) and energy efficiency (EE) (r = .99).It has also been shown that the TPC correlates with antioxidant activity, whether with DPPH (r = .79) or ABTs (r = .90). Similar results have been found by many researchers, namely,Zhao, Yang, Wang, and Lu (2009),Bushra (2012),Lim, Pang, Yusoff, Mudalip, andGimbun (2019), andHimed-Idir et al (2021). Nevertheless,Zheng and Wang (2001) suggested that not only the level of antioxidants but also a synergy between them and other plant constituents could influence the difference in the antioxidant capacity of plant extracts.…”
supporting
confidence: 84%
“…Rosmarinus officinalis L. extract has been proposed as a possible therapeutic agent for many diseases [16]. Rosemary powder and its lyophilized ethanolic extract at different concentrations were used to formulate fresh cheeses, wherein the plant extract improved phenolics content and antioxidant capacity compared to the control cheese [17]. This study focused on enhancing the functional properties of yoghurt with the addition of different concentrations of rosemary extracts.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of boundary lines in the refraction field was observed and recorded, and the refractive index was identified [ 30 ]. The amount of fat was determined by following the Garber protocol [ 31 ], and the amount of energy was determined by following the procedure outlined in the Malaysian food composition database [ 32 ]. The Formulas (2 and 3) used to calculate energy (kcal) are as follows: Energy, kcal/100 g = [Fat] × 9 + [Protein] × 4 + [Carbohydrate] × 4 Energy, kJ/100 g = kcal × 4.184 …”
Section: Methodsmentioning
confidence: 99%